2008
DOI: 10.1080/08957340802558342
|View full text |Cite
|
Sign up to set email alerts
|

Item Position and Item Difficulty Change in an IRT-Based Common Item Equating Design

Abstract: In operational testing programs using item response theory (IRT), item parameter invariance is threatened when an item appears in a different location on the live test than it did when it was field tested. This study utilizes data from a large state's assessments to model change in Rasch item difficulty (RID) as a function of item position change, test level, test content, and item format. As a follow-up to the real data analysis, a simulation study was performed to assess the effect of item position change on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
53
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(63 citation statements)
references
References 13 publications
8
53
0
2
Order By: Relevance
“…Traditionally, two kinds of item‐position effects have been discerned (Kingston & Dorans, ): a practice or a learning effect occurs when the items become easier in later positions, and a fatigue effect occurs when items become more difficult if placed towards the end of the test. Recent empirical studies on the effect of item position include Hohensinn et al (), Meyers, Miller, and Way (), Moses, Yang and Wilson (), Pommerich and Harris (), and Schweizer, Schreiner and Gold ().…”
mentioning
confidence: 99%
“…Traditionally, two kinds of item‐position effects have been discerned (Kingston & Dorans, ): a practice or a learning effect occurs when the items become easier in later positions, and a fatigue effect occurs when items become more difficult if placed towards the end of the test. Recent empirical studies on the effect of item position include Hohensinn et al (), Meyers, Miller, and Way (), Moses, Yang and Wilson (), Pommerich and Harris (), and Schweizer, Schreiner and Gold ().…”
mentioning
confidence: 99%
“…In these studies, exarninee effort is cornrnonly seen as constant throughout the assessrnent. However, research has shown that perforrnance in large-scale assessrnents can decrease (e.g., Hohensinn et al, 2008;Meyers, Miller, & Way, 2009), possibly due to fatigue or a decline in rnotivation. Hence, it seerns likely that, during testing, a change in examinee effort can take place.…”
mentioning
confidence: 99%
“…For example, the difficulty of an item can increase in later positions due to a fatigue effect or decreasing test-taking effort (Hohensinn et al 2011;Weirich et al 2016). To investigate item position effects, researchers have proposed different approaches using logistic regression (e.g., Davey and Lee 2011;Pomplun and Ritchie 2004), multilevel IRT models based on the GLMM framework (e.g., Albano 2013; Li et al 2012;Weirich et al 2014), and test equating (e.g., Pommerich and Harris 2003; Meyers et al 2009;Store 2013). The purpose of the current study was to introduce a factor analytic approach for modeling item position effects using the SEM framework.…”
Section: Discussionmentioning
confidence: 99%
“…To date, three different methodological approaches for investigating item position effects have been described: (1) logistic regression models (e.g., Davey and Lee 2011;Pomplun and Ritchie 2004;Qian 2014); (2) multilevel models based on the generalized linear mixed modeling (GLMM) framework (e.g., Albano 2013; Alexandrowicz and Matschinger 2008;Debeer and Janssen 2013;Hartig and Buchholz 2012;Li et al 2012;Weirich et al 2014); and (3) test equating methods (e.g., Kingston and Dorans 1984;Kolen and Harris 1990;Moses et al 2007;Pommerich and Harris 2003;Meyers et al 2009;Store 2013). Although there are some empirical studies that used the factor analytic methods for modeling position effects (e.g., Bulut et al 2016;Schweizer 2012;Schweizer et al 2009), the current study represents the first study that utilized the SEM framework as a methodological approach for examining item position effects.…”
Section: Comparison With Other Approachesmentioning
confidence: 99%
See 1 more Smart Citation